2022
DOI: 10.1007/s15010-022-01889-6
|View full text |Cite
|
Sign up to set email alerts
|

High burden of RSV hospitalizations in Germany 2021–2022

Abstract: Background Public health measures implemented to mitigate the effects of the COVID-19 pandemic disrupted the worldwide transmission of endemic respiratory viruses such as RSV, as well as other typical, seasonal, and viral respiratory pathogens. Methods From October 18, 2021 to March 31, 2022, RSV cases admitted to German pediatric hospitals were monitored via a newly established, national, Clinician-Led Reporting System (CLRS) that recorded patient age and type of respiratory support. A subanalysis of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…In the sense of effectiveness of face masks in the real-world setting (cost-benefit), the mask should show a benefit in terms of reduced respiratory infections, e.g., in healthcare through fewer consultations or hospitalizations ( 192 ). Unfortunately, this was not the case, e.g., in Germany ( 193 ) and USA ( 194 ), where mask mandates were ubiquitous ( 9 ). Additionally, there is evidence that COVID-19 rates have been able to expand swiftly when omicron hit ( 178 ) even in societies where mask use was assiduously followed—as in Korea, Taiwan, Hong Kong, and Singapore ( 179 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the sense of effectiveness of face masks in the real-world setting (cost-benefit), the mask should show a benefit in terms of reduced respiratory infections, e.g., in healthcare through fewer consultations or hospitalizations ( 192 ). Unfortunately, this was not the case, e.g., in Germany ( 193 ) and USA ( 194 ), where mask mandates were ubiquitous ( 9 ). Additionally, there is evidence that COVID-19 rates have been able to expand swiftly when omicron hit ( 178 ) even in societies where mask use was assiduously followed—as in Korea, Taiwan, Hong Kong, and Singapore ( 179 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot conclude that the RSV infections were more severe than before Covid-19. A study from Germany confirmed a higher RSV hospitalization rate than in previous years and an increase in RSV infection rates in 2-to 4-year-old children (25).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, during the COVID-pandemic, nonpharmaceutical interventions (general preventive and hygienic measures, such as physical distancing and face masks and sensibilization campaigns) against the transmission of SARS-CoV-2 also (temporarily) mitigated the burden of RSV and distorted the normal timing of RSV infections. [47][48][49] These interventions also have the potential to reduce RSV transmission to protect the most vulnerable. On the other hand, infection prevention without the build-up of immunity (eg, through immunization) may have contributed to the high RSV burden in Europe in autumn 2022 and may increase the susceptibility to severe disease later.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, infection prevention without the build-up of immunity (eg, through immunization) may have contributed to the high RSV burden in Europe in autumn 2022 and may increase the susceptibility to severe disease later. 47,49 This study is, to the best of our knowledge, the first to use population-wide representative data to describe the organizational burden of RSV and to quantify the impact of RSV-associated hospitalizations on pediatric bed occupancy. The activity peak in pediatric services is to a large extent driven by the seasonal surge in RSV-associated hospitalizations, with RSV-associated hospitalizations accounting for 20%-40% of bed capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation